Borophene: Stretch‐Driven Increase in Ultrahigh Thermal Conductance of Hydrogenated Borophene and Dimensionality Crossover in Phonon Transmission (Adv. Funct. Mater. 31/2018). (30th July 2018) - Li, Dengfeng; He, Jia; Ding, Guangqian; Tang, QiQi; Ying, Yan; He, Junjie; Zhong, Chengyong; Liu, Yi; Feng, Chunbao; Sun, Qilong; Zhou, Hangbo; Zhou, Ping; et al.
Abstract : Interestingly and in contrast to widely perceived sense, the room temperature thermal conductance of hydrogenated borophene in the armchair direction is found to be remarkably larger than that of graphene. In article number1801685, Dengfeng Li, Gang Zhang, and co‐workers demonstrate a dimensionality crossover in phonon transmission where low frequency phonons exhibit 2D characteristics, while high frequency phonons exhibit 1D characteristics.